Ear Replantation Using Superficial Temperoparietal Fascia Flap Without Microvascular Surgery: A Case Report (Annals of Medical Research, 2021)
None
Keywords: Ear amputation, Superficial temporoparietal fascia, Ear replantation without microsurgery